Assessment of earthquake-induced ground liquefaction susceptibility for Hanoi city using geological and geomorphologic characteristics - Nhung*, Bui Thi; Phuong, Nguyen Hong; Nam, Nguyen Ta (Vietnam Journal of Earth Sciences, 2017)
In this paper, the earthquake-induced liquefaction susceptibility of Hanoi city is assessed using the recent published geological and geomorphologic data. A combination of classification methods based on the distribution of sedimentary deposits proposed by Youd and Perkins (1978) and geomorphologic units proposed by Iwasaki (1982) was applied. The subsurface lithology and geomorphologic maps were combined in a GIS platform for assessing the liquefaction susceptibility of Hanoi city. The resulting map shows that the liquefaction hazard of Hanoi city classified into four categories: high, moderate, low liquefaction potential and not likely areas. In the most of Hanoi area, the ground liquefaction potentials are moderate. The high liquefaction likely areas spread along the river beds and around the lake areas. The not likely and low liquefaction potential areas are observed mainly in the northwest and northeast of the study region such as Chanchim, Soc Son, and Bavi mountains. The present map can help the scientists, engineers, and planners to have the general information on regional liquefaction potential of the Hanoi city. References Bird JF, Bommer JJ, 2004b. Earthquake Losses due to Ground Failure. Submitted to Engineering Geology, 75(2), 147-179. Bird Juliet F, Bommer Julian J., 2004a. Evaluating earthquake losses due to ground failure and identifying their relative contribution (Paper no. 3156). In Proceedings of the 13th world conference on earthquake engineering, Vancouver, B.C., Canada, august 1-6. Bui Van Duan, Nguyen Cong Thang, Nguyen Van Vuong, Pham Dinh Nguyen, 2013. The magnitude of the largest possible earthquake in the Muong La-Bac Yen fault zone. J. Sci. of the Earth, 35(1), 53-59. Dao Dinh Bac, Dang Van Bao, 2010. Geomorphologic characteristics, the ancient river beds system of the capital city and their values to the development of the Thang Long - Hanoi. International Workshop commemorating the 1000 years of Thang Long, Hanoi. Vietnam national University, Hanoi. Ganapathy, G. P., Rajawat, A. S., 2012. Evaluation of liquefaction potential hazard of Chennai city, India: using geological and geomorphological characteristics. Natural hazards, 64(2), 1717-1729. Goyal, A., Sinha, R., Chaudhari, M. and Jaiswal, K., 2001. Performance of Reinforced Concrete Buildings in Ahmedabad during Bhuj Earthquake January 26, 2001. Workshop on Recent Earthquakes of Chamoli and Bhuj: Volume I, Roorkee, India, May 24-26. Iwasaki, T., Tokida, K., Tatsuoka, F., Watanabe, S., Yasuda, S., Sato, H., 1982. Microzonation for soil liquefaction potential using simplified methods. In Proceedings of the 3rd international conference on microzonation, Seattle, 3, 1310-1330. Kuribayashi E., Tatsuoka, F., 1975. Brief review of liquefaction during earthquake in Japan,” Soils and Foundations, 15(4), 81-92. Lew M, Naeim F, Huang SC, Lam HK, Carpenter LD, 2000. Geotechnical and geological effects of the 21 September 1999 Chi-Chi earthquake, Taiwan. Structural Design of Tall Buildings, 9, 89-106. National Research Council, 1985. Ishihara 1985. Liquefaction of Soils During Earthquake, National Academy press, 240, p.34. Nguyen Hong Phuong (Project Manager), 2002. Study of seismic risk of Hanoi city. Project code 01C-04/09-2001-2. Institute for Marine Geology and Geophysics, VAST. Nguyen Hong Phuong (Project Manager), 2007. Application of GIS technology to Development of a model for seismic risk analysis for Hanoi city. Institute for Marine Geology and Geophysics, VAST. Nguyen Hong Phuong (Project Manager), 2014. Estimation of Site Effects and Assessment of Urban Seismic Risk for Hanoi city. National Scientific Research Project Final report, Institute of Geophysics, VAST. Nguyen Hong Phuong and Pham The Truyen, 2014. Probabilistic seismic hazard assessment for South Central Vietnam. J. Sci. of the Earth, 36(4), 451-461. Phan Trong Trinh, Hoang Quang Vinh, Nguyen Van Huong, Ngo Van Liem, 2013. Active fault segmentation and seismic hazard in Hoa Binh reservoir, Vietnam. Cent. Eur. J. Geosci, 5(2), 223-235. Phan Trong Trinh, Ngo Van Liem, Nguyen Van Huong, Hoang Quang Vinh, Bui Van Thom, Bui Thi Thao, Mai Thanh Tan, Nguyen Hoang, 2012. Late Quaternary tectonics and seismotectonics along the Red River fault zone, North Vietnam. Earth-Science Reviews 114, 224-235. <a href="file://localhost/Susumu%2520Yasuda,%2520Nozomu%2520Yoshida,%2520Hiroyoshi%2520Kiku,%2520Hidenori%2520Abo,%2520and%2520Masato%2520Uda,%25202001.%2520Analyses%2520of%2520Liquefaction-Induced%2520Deformation%2520of%2520Grounds%2520and%2520Structures%2520by%2520a%2520Simple%2520Method%2520(March%252026).%2520International%2520Conferences%2520on%2520Recent%2520Advances%2520in%2520Geotechnical%2520Earthquake%2520Engineering%2520and%2520Soil%2520Dynamics,%2520p.27.%2520http/::scholarsmine.mst.edu:icrageesd:04icrageesd:session04:27.">Susumu Yasuda, Nozomu Yoshida, Hiroyoshi Kiku, Hidenori Abo, and Masato Uda, 2001. Analyses of Liquefaction-Induced Deformation of Grounds and Structures by a Simple Method (March 26). International Conferences on Recent Advances in Geotechnical Earthquake Engineering and Soil Dynamics, p.27. http://scholarsmine.mst.edu/icrageesd/04icrageesd/session04/27. Updike, R. G., Egan, J. A., Moriwaki, Y., Idriss, I. M., Moses, T. L., 1988. A model for earthquake-induced translatory landslides in Quaternary sediments. Geological Society of America Bulletin, 100(5), 783-792. Vu Thanh Tam (Project Manager), 2014. Study and propose a reasonable threshold for preventing the subsidence caused by ground water exploitation, pilot application for downtown area of the Hanoi city. Final report of the Scientific research and technology development Project, National Center for water resource planning and investigation. Ministry of Natural Resources and Environment. Youd T. L., 1993. Liquefaction, ground failure and consequent damage during the 22 April 1991 Costa Rica earthquake. Abridged from EERI Proceedings: U.S. Costa Rica Workshop, http://nisee.berkeley.edu/costarica/ Youd T. L., and Hoose S.N., 1977. Liquefaction Susceptibility and Geologic Setting, Proceedings, 6th World Conference on Earthquake Engineering, New Delhi, India, 6, 37-42. Youd T. L., and Perkins D. M., 1978. Mapping liquefaction-induced ground failure potential. Journal of the Geotechnical Engineering Division, ASCE, 104, GT4, 433-446.